Multiscale in-situ quantification of the role of surface roughness and contact area using a novel Mica-PVS triboelectric nanogenerator. (March 2023) - Kumar, Charchit; Perris, Jack; Bairagi, Satyaranjan; Min, Guanbo; Xu, Yang; Gadegaard, Nikolaj; Mulvihill, Daniel M.
Abstract: Triboelectric nanogenerators (TENGs) are energy harvesters generating electricity via the triboelectric effect and electrostatic induction. However, the influence of interface mechanics on TENG performance requires attention. Here, we study the effect of random multiscale surface roughness on TENG performance using a novel in-situ optical technique to directly visualise the contact interface. To achieve this, a new type of TENG is developed based on transparent mica in contact with polyvinyl siloxane (PVS). A wide range of surface roughness instances were created on the PVS surface ( Sq from 1.5 to 82.5 µm) by replicating 3D-printed masters developed from numerically generated rough surfaces. TENG output was found to be highly sensitive to surface roughness over a wide range of forces and frequencies. The dependence of real contact area on roughness was identified as the underlying cause. In this work, electrical output (and contact area) decreased significantly with increasing roughness. The highest output (smoothest PVS surface) gave open circuit voltage 222.8 V, short-circuit current density 53 mA/m 2 and peak-power density 4256 mW/m 2 : a competitive output given the rapid and simple fabrication, low cost and long durability demonstrated. The new Mica-PVS TENG, the direct technique for TENG interface visualisation and the insights on the role of topography and contact area will be invaluable for future TENG design. Graphical Abstract: ga1 Highlights: New high-performance TENG based on PVS in contact with mica. Competitive output (4256 mW/m 2 ) despite cost effective and simple manufacture. Optical technique for TENG interface visualisation & contact area measurement. Comprehensive study on the effect of multiscale surface roughness on TENG output. Output decreases with increasing roughness due to contact area reduction.